2020
DOI: 10.3390/f11080789
|View full text |Cite
|
Sign up to set email alerts
|

Development of Comprehensive Fuel Management Strategies for Reducing Wildfire Risk in Greece

Abstract: A solution to the growing problem of catastrophic wildfires in Greece will require a more holistic fuel management strategy that focuses more broadly on landscape fire behavior and risk in relation to suppression tactics and ignition prevention. Current fire protection planning is either non-existent or narrowly focused on reducing fuels in proximity to roads and communities where ignitions are most likely. A more effective strategy would expand the treatment footprint to landscape scales to reduce fire intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 78 publications
0
34
0
1
Order By: Relevance
“…Science can contribute with knowledge and tools for more effective landscape fuel management, thus improving planning and decision-making. Previous research has shown how fire spread simulation tools can be used to assess wildfire exposure at the landscape level [19][20][21], quantify associated risk [22][23][24], study wildfire transmission [25,26] and identify optimal fuel treatment location [27,28]. These simulation tools have also proven useful to quantify the potential impact of climate change on wildfire incidence [29] and of mitigation measures on post-fire erosion and water contamination [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Science can contribute with knowledge and tools for more effective landscape fuel management, thus improving planning and decision-making. Previous research has shown how fire spread simulation tools can be used to assess wildfire exposure at the landscape level [19][20][21], quantify associated risk [22][23][24], study wildfire transmission [25,26] and identify optimal fuel treatment location [27,28]. These simulation tools have also proven useful to quantify the potential impact of climate change on wildfire incidence [29] and of mitigation measures on post-fire erosion and water contamination [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…É importante decatarse de que a nova situación require actuar sobre os combustibles a escala da paisaxe xa que é o escenario onde resulta esencial alterar a conectividade dos combustibles (Viedma et al 2009, Ager et al 2017, Alcasena et al 2019, Martín-Martín et al 2013, Salis et al 2018, Sil et al 2019, Palaiologou et al 2020) para poder influír en incendios como os dos eventos extremos, que desenvolven tamén unha dinámica de propagación a grande escala, cunha enorme potencia e que posiblemente tenderán a incrementarse cada vez máis, probablemente involucrando de forma crecente áreas habitadas. Iso esixe accións transversais de coordinación de diferentes departamentos da Administración e priorización dos criterios de prevención de incendios nas diferentes actuacións levadas a cabo por eles.…”
Section: Algunhas Consideracións E Propostas De Adaptación Ao Novo Escenariounclassified
“…Megafires, often defined as burning more than 10,000 ha (100 km 2 ), consume large amounts of biomass, and release huge amounts of greenhouse gases to the atmosphere [ 5 ]. Due to climate change, the megafires are intensified and the fire seasons prolonged, creating increasing challenges for fire management [ 6 , 7 ]. “Climate-fuelled megafires” have, therefore, gained global attention.…”
Section: Introductionmentioning
confidence: 99%